Electromagnetic thermal coupling analysis for a novel cooling system of an axial flux hub motor - Jiujian Chang; Chen Wang (IET Electric Power Applications, 2022)
Abstract In this paper, a novel cooling system of the yokeless and segmented armature axial flux machine (YASA) applied in‐wheel traction is presented. Although the cooling system has high cooling efficiency, it will deteriorate the electromagnetic characteristics of the motor. The eddy current analysis for the prototype is performed based on the 3‐D finite‐element method, and the distribution of eddy current in the cooling fins is presented. Through the 2‐D finite element analysis, the cause of the eddy current loss of the fin is revealed. In order to increase the output power of the motor, the height of the fin in the axial direction is optimised by the magneto‐thermal coupling method. And finally, the hub motor is manufactured and tested. It can be concluded that the measured data matched well with the analysis results.